Impacto socioeconómico del centro de rehabilitación social y su incidencia en la seguridad ciudadana en el cantón Latacunga, provincia de Cotopaxi - Escobar Chiliquinga, Beatriz Jimena (2015)
This research aimed to inquire about what was the socioeconomic impact caused by the Social Rehabilitation Center of Latacunga Canton, because this has caused many problems in society, since security is a key factor that helps to prevail physical integrity, economic and trade of citizens. For this reason the methodology used was a quantitative and qualitative approach, since percentages are used to measure the socio-economic indices, subsequently an analysis was performed to obtain a better understanding of what is taking place in this research….